Novel weapon-aided plant protection in the underground battlefield - Seonghan Jang; Jin-Soo Son; Eric A Schmelz; Choong-Min Ryu (Plant Signaling & Behavior)
Ralstonia solanacearum and R. pseudosolanacearum, the causative agents of bacterial wilt, ranks as the second most devastating phytopathogens, affecting over 310 plant species and causing substantial economic losses worldwide. R. solanacearum and R. pseudosolanacearum infect plants through the underground root system, where it interacts with both the host and the surrounding microbiota and multiply in the xylem where bacteria cell and its polysaccharide product block the water transportation from root to aboveground. Currently, effective control methods are limited, as resistance genes are unavailable and antibiotics prove ineffective. In current Commentary, we review recent advancements in combating bacterial wilt, categorizing the approaches (weapons) into three distinct strategies. The physical and chemical weapons focus on leveraging sound waves to trigger crop immunity and reducing bacterial virulence signaling, respectively. The biological weapon employs predatory protists to directly consume Ralstonia cells in the root zone, while also reshaping the protective rhizosphere microbiome to fortify the plant. We believe that these novel methods hold the potential to revolutionize crop protection from bacterial wilt and inspire new era in sustainable agriculture.